988 Anxiety among health care workers of a teaching hospital. (24th April 2018) - Pougnet, R; Verdier, G; Saliou, P; Dantec, F; Eniaffe, B; Durand-Moreau, Q; Loddé, B; Dewitte, JD
Abstract : An investigation in psychological suffering in all hospital workers of a teaching hospital has been conducted during one month. Population and methods: Our population was composed of 5792 non medical professionals of a teaching universitary hospital. 1738 workers were randomly selected, and answered an online auto-questionnaire, consisting of 4 parts: socio-professional data; JCQ questionnaire (Karasek); HAD questionnaire and working experience scale. Data were collected on Sphinx Online R software and exploited on Excel, using Chi2 statistical test with p<0.05. Results: In this study, 822 questionnaires were exploitable, representing 47.3% of the population, and including 81.3% of women. The mean age was 41.8 years old, and workers were 84.3% permanent staff. Job strained staff represented 51.7% of the population, whereas 33.7% of the staff were in active. The overall isostrain was 31.6%. More permanent workers, nurse's aide and hospital keener were job strained (p<0.05). Depression prevalence was of 8%: men, technical agents and people between 42 and 50 years old had a higher risk of depression, respectively 13%, 15.3% and 13.4% (p<0.05). Anxiety prevalence was of 21.6%: agents before 42 and 50 years old, permanent workers, nurse's aide, had an increased risk of presenting anxious disorder, respectively 28.2%, 22.9% and 28/3% (p<0.05). Conclusion: Anxiety and depression prevalences were important in this study, in a hospital environment, and were higher than in general population. High level of psychological demand partly explained those prevalences.